Antiproliferative activity of platinum(II) complexes containing triphenylphosphine: Correlation between structure and biological activity. (8th January 2015) - Belli Dell' Amico, Daniela; Dalla Via, Lisa; García-Argáez, Aída Nelly; Labella, Luca; Marchetti, Fabio; Samaritani, Simona
Abstract : Graphical abstract: A series of neutral platinum (II) complexes bearing triphenylphosphine (1 –7 ) were tested in vitro against HeLa, H460 and A549 tumor cells. The preparation and the X-ray structures of new complexes2 and7 were described. A brief discussion regarding the correlation between the structure and the antiproliferative activity is presented. Abstract: A series of neutral complexes of platinum(II) of general formula [PtCl2 L(PPh3 )] [L = Et2 NC(Me)NH, SOMe2, CO, Et2 NH, (HOCH2 CH2 )2 NH, Bz2 NH, N-morpholine] was prepared starting from suitable precursors. The syntheses and spectroscopic characterizations of the two new complexes trans -[PtCl2 (N-morpholine)(PPh3 )] and cis -[PtCl2 (SOMe2 )(PPh3 )] are described as well as their X-ray structures. The antiproliferative activity of all the available compounds was tested in vitro against HeLa, H460 and A549 human tumor cell lines. A brief discussion regarding the structure–activity correlation is presented.